Studies and Rejection of Intercrystal Crosstalk on FPGA in a High-Energy Photon-Counting System - Jiahao Chang; Huaxia Zhang; Shibo Jiang; Zhifang Wu; Shuo Xu (Applied Sciences)
Intercrystal scatter reduces system sensitivity and spatial resolution, a phenomenon that has been extensively studied in positron emission tomography (PET) systems. However, the issue is even more significant in high-energy systems. The purpose of this study is to propose a practical crosstalk rejection technique and demonstrate its applicability in high-energy photon-counting systems. The effect of inter-crystal scattering interactions between 60Co γ photons and lutetium yttrium oxyorthosilicate (LYSO) scintillator crystals is investigated through Monte Carlo simulations conducted using the Geant4 toolkit. To suppress the crosstalk phenomenon, a field-programmable gate array (FPGA)-based algorithm is proposed to suppress inter-crystal scattering events, characterized by a time window of 5 nanoseconds and detector window sizes of one or two. The 250 mm Fe steel penetration model is used to evaluate the proposed algorithm, showing improved radiation image quality, particularly with a detector window size of two, which performs better under low-count-rate conditions. Laboratory testing indicates that the proposed algorithm can enhance steel penetration (SP) by 60–70 mm of Fe when compared to the existing current integration system under the same settings. The suggested method has been proven effective in producing higher-quality images and demonstrates good adaptability by adapting the detector window width according to different system count rates.